Eye-Movement Control in RAN and Reading - Kuperman, Victor; Van Dyke, J. A.; Henry, R. (Taylor & Francis, 2016)
The present study examined the visual scanning hypothesis, which suggests that fluent oculomotor control is an important component underlying the predictive relationship between Rapid Automatized Naming (RAN) tasks and reading ability. Our approach was to isolate components of saccadic planning, articulation, and lexical retrieval in 3 modified RAN tasks. We analyzed 2 samples of undergraduate readers (ages 17–27). We evaluated the incremental contributions of these components and found that saccadic planning to nonlinguistic stimuli alone explained roughly one third of the variance that conventional RAN tasks explained in eye movements registered during text reading for comprehension. We conclude that the well-established predictive role of RAN for reading performance is in part due to the individual ability to coordinate rapid sequential eye movements to visual nonlinguistic stimuli.
Keywords: Eye-movements; Rapid automatized naming; Reading ability